2006
DOI: 10.3758/bf03194010
|View full text |Cite
|
Sign up to set email alerts
|

The number line effect reflects top-down control

Abstract: Human attention is normally conceived as a limited capacity process that can be controlled in either an exogenous, reflexive manner or an endogenous, volitional manner (Broadbent, 1971;Posner, 1978). For several decades, the attention-cuing paradigm has provided a simple methodology for engaging and measuring these two forms of orienting (Posner, 1980;Posner, Snyder, & Davidson, 1980). Typically, reflexive attention has been triggered by a peripheral flash that does not predict where a visual target will appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 19 publications
12
126
3
Order By: Relevance
“…One first striking finding is that digits were ineffective in orienting attention when directly compared with eye gaze and arrows. The absence of cueing effect for digits seems to be at odds with the findings of Fischer et al (2003), but it is consistent with the results of recent studies on healthy participants (Casarotti, Michielin, Zorzi, & Umiltà, 2007;Galfano, Rusconi, & Umiltà, 2006;Ristic, Wright, & Kingstone, 2006). All these studies support the view that digits possess a low degree of automaticity in the hierarchy of cues that, although irrelevant for the task, can orient attention.…”
Section: Discussionsupporting
confidence: 51%
“…One first striking finding is that digits were ineffective in orienting attention when directly compared with eye gaze and arrows. The absence of cueing effect for digits seems to be at odds with the findings of Fischer et al (2003), but it is consistent with the results of recent studies on healthy participants (Casarotti, Michielin, Zorzi, & Umiltà, 2007;Galfano, Rusconi, & Umiltà, 2006;Ristic, Wright, & Kingstone, 2006). All these studies support the view that digits possess a low degree of automaticity in the hierarchy of cues that, although irrelevant for the task, can orient attention.…”
Section: Discussionsupporting
confidence: 51%
“…For example, when asked to imagine numbers on a clock-face, number cues induces attentional shifts in accordance with the position of the number on the clock (Ristic, Wright, & Kingstone, 2006). Similarly, when providing the direct instruction to associate small numbers with right and large numbers with left, the number-based attentional cueing effect reverses as well (Galfano, Rusconi, & Umilta, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, while mapping small numbers to the beginning and large numbers to the end of the memorized sequence may be the default association, this can be easily changed by the instructions given to the participants (e.g. the request to imagine the numbers as hours on a clock-face, Ristic et al, 2006;or to associate small numbers with a right location and large numbers with a left one, Galfano, et al, 2006). Again, whereas the mental number line account has difficulties to explain these findings, the flexible nature of WM can easily account for these observations.…”
Section: Memorymentioning
confidence: 99%
“…Interestingly, the mental number line does not only influence overt spatial responses but it also exerts an effect on the allocation of spatial attention prior to any explicit response (although it is still subject to debate whether this effect is automatic or susceptible of top-down control, cf. Galfano et al, 2006;Ristic et al, 2006). For instance, Fischer et al (2003) found that exposure to small numbers (1 or 2) preceding the presentation of the target stimulus in a simple visual detection task facilitated detection of target appearing in the left hemifield, while exposure to large numbers (8 or 9) facilitated target detection in the right hemifield (see also Stoianov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%